Ferroelectric film and electronic components

A hafnium oxide-based ferroelectric film with controlled carbon content and metal oxide additives addresses leakage current issues, ensuring high insulation and ferroelectricity, thus stabilizing transistor performance.

JP7612177B2Active Publication Date: 2025-01-14MURATA MFG CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023548503
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-17
Filing Date
2022-09-15
Publication Date
2025-01-14
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

Hafnium oxide thin films used in ferroelectric gate transistors face challenges in maintaining ferroelectricity and high insulation properties, leading to leakage current issues that hinder reliable transistor operation.

Method used

A ferroelectric film composed of hafnium oxide with a fluorite structure and metal oxides containing La, Ce, and Bi, with carbon content limited to less than 5 mol%, is manufactured using a spin-coating method under an oxygen atmosphere, resulting in a polycrystalline film with an average particle size of less than 10 nm.

Benefits of technology

The solution achieves a ferroelectric film with enhanced ferroelectricity and high insulation properties, reducing leakage current to 9.7 x 10^-8 A/cm^2 at 1 MV/cm, enabling stable transistor operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612177000001
    Figure 0007612177000001
  • Figure 0007612177000002
    Figure 0007612177000002
  • Figure 0007612177000003
    Figure 0007612177000003
Patent Text Reader

Abstract

The present disclosure provides: a ferroelectric film exhibiting ferroelectricity and having high insulation properties; a method for manufacturing the ferroelectric film; and, an electronic component. The present disclosure is a ferroelectric film that contains hafnium oxide (HfO2). The ferroelectric film contains hafnium oxide (HfO2), a metal oxide, and carbon. The hafnium oxide (HfO2) has a fluorite structure. The metal oxide has one element or a plurality of elements selected from La, Ce, and Bi. The amount of carbon included is less than 5 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a ferroelectric Membrane, and electronic components. [Background technology]

[0002] Ferroelectric gate transistors (Fe-FETs: Ferroelectric Field-Effect Transistors), which use ferroelectrics as the gate insulating film, are used in memory elements of IC (Integrated Circuit) cards, etc. It is generally known that the ferroelectric properties of ferroelectrics weaken as they are miniaturized and made thinner, and this property makes it difficult to miniaturize and highly integrate ferroelectric gate transistors as memory elements.

[0003] In recent years, it has been reported that thin films of hafnium oxide (HfO2) exhibit ferroelectricity, and various research and development efforts have been conducted on hafnium oxide thin films. Specifically, Patent Document 1 discloses a capacitor using a thin film of hafnium oxide. Furthermore, Non-Patent Document 1 reports that a ferroelectric substance applicable to ferroelectric gate transistors has been obtained by heat-treating a thin film of hafnium oxide in a vacuum. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 208340 [Non-patent literature]

[0005] [Non-Patent Document 1] Mohit, et al. "Indium oxide and indium-tin-oxide channel ferroelectric gate thin film transistors with yttrium doped hafnium-zirconium dioxide gate insulator prepared by chemical solution process", Japanese Journal of Applied Physics, Japan, 15 January 2021. Volume 60, Number SBBM02. Summary of the Invention [Problem to be solved by the invention]

[0006] However, when a hafnium oxide thin film is used in an electronic component such as a ferroelectric gate transistor, it is necessary for the thin film to have high insulating properties as well as ferroelectricity. For example, when a hafnium oxide thin film is used as the gate insulating film of a ferroelectric gate transistor, if leakage current occurs in the hafnium oxide thin film, reliable transistor operation cannot be obtained.

[0007] Therefore, an object of the present disclosure is to provide a ferroelectric material that exhibits ferroelectricity and has high insulating properties. Membrane, and electronic components. [Means for solving the problem]

[0008] A ferroelectric film according to an embodiment of the present disclosure includes hafnium oxide having a fluorite structure, a metal oxide having one or more elements selected from La, Ce, and Bi, and carbon contained in an amount of less than 5 mol %. fruit, Polycrystalline with an average particle size of less than 10 nm .

[0009] An electronic component according to an embodiment of the present disclosure includes the above-described ferroelectric film and an electrode formed on a surface of the ferroelectric film.

[0010] A manufacturing method according to one embodiment of the present disclosure is a method for manufacturing a ferroelectric film containing hafnium oxide. The manufacturing method includes the steps of preparing a film-forming target, preparing a chemical solution serving as a raw material for the ferroelectric film, spin-coating the chemical solution onto the film-forming target, and precipitating hafnium oxide having a fluorite structure from the chemical solution spin-coated on the film-forming target by heat treatment in an oxygen atmosphere. The chemical solution contains, as raw material salts, a metal alkoxide salt containing Hf and a metal alkoxide salt containing one or more elements selected from La, Ce, and Bi. [Effects of the Invention]

[0011] According to one embodiment of the present disclosure, by making the carbon content less than 5 mol %, it is possible to obtain a ferroelectric film that exhibits ferroelectricity and also has high insulating properties. [Brief explanation of the drawings]

[0012] [Figure 1] 1 is an X-ray diffraction spectrum of a ferroelectric film according to an embodiment. [Figure 2] 10 is a polarization-electric field curve of a ferroelectric film according to an embodiment. [Figure 3] 10 is a leakage current-electric field curve of a ferroelectric film according to an embodiment. [Figure 4] 10 is a polarization-electric field curve of a comparative ferroelectric film. [Figure 5] 1A and 1B are diagrams illustrating a capacitor using a ferroelectric film according to an embodiment. [Figure 6] 1A and 1B are diagrams illustrating a transistor using a ferroelectric film according to an embodiment. [Figure 7] 10A and 10B are diagrams showing electrical characteristics of a transistor using a ferroelectric film according to an embodiment. DETAILED DESCRIPTION OF THE INVENTION

[0013] (Embodiment) Hereinafter, a ferroelectric film, a manufacturing method thereof, and an electronic component according to the present embodiment will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are designated by the same reference numerals, and description thereof will not be repeated.

[0014] [Ferroelectric film] First, the ferroelectric film according to the embodiment will be described. The ferroelectric film is a thin film of hafnium oxide (HfO2), and in order to exhibit ferroelectricity, the hafnium oxide has a fluorite structure. FIG. 1 shows an X-ray diffraction spectrum of the ferroelectric film according to the embodiment. In FIG. 1, the horizontal axis represents angle, and the vertical axis represents intensity. The diffraction lines appearing near 30° and 35° in FIG. 1 can be attributed to a cubic, tetragonal, or orthorhombic fluorite structure, and it can be seen that the ferroelectric film according to the embodiment contains hafnium oxide having a fluorite structure.

[0015] Since pure HfO2 film does not exhibit ferroelectricity, it is necessary to include element-substituted metal oxides. 4+ ) is preferred, and it is effective to include a metal oxide substituted with an element such as La, Ce, or Bi. The ferroelectric film according to this embodiment includes a metal oxide having one or more elements selected from La, Ce, and Bi. The X-ray diffraction spectrum shown in FIG. 1 confirms that a HfO2 film with a fluorite structure substituted with Ce has been formed. The content of the metal oxide substituted with an element such as La, Ce, or Bi is preferably 1 mol % or more and 15 mol % or less.

[0016] Next, the electric field characteristics of polarization of the ferroelectric film according to the present embodiment will be described. membrane2 shows a polarization-electric field curve. In FIG. 2, the horizontal axis represents the electric field, and the vertical axis represents the polarization. Generally, when the polarization-electric field curve changes so that a polarization history occurs with respect to the electric field, the insulating film can be determined to have ferroelectricity. Specifically, in FIG. 2, the polarization (remanent polarization) when the electric field is changed from 0 MV / cm to approximately 3 MV / cm and then returned to 0 MV / cm corresponds to the spontaneous polarization Ps, and a polarization of approximately 10 μC / cm2 occurs in the film. In other words, FIG. 2 shows that the ferroelectric film according to this embodiment has ferroelectricity.

[0017] Furthermore, in the ferroelectric film according to this embodiment, the leakage current can be reduced by making the carbon content less than 5 mol%. Until now, the cause of the large leakage current of a ferroelectric film was unknown, but in this disclosure, we have focused on the carbon content and found that the carbon content affects the leakage current of a ferroelectric film. In other words, in the ferroelectric film according to this embodiment, by reducing the carbon content, the leakage current of the ferroelectric film is suppressed to a desired current value or less.

[0018] The amount of carbon contained in the ferroelectric film can be measured, for example, by secondary ion mass spectrometry (SIMS). The ferroelectric film according to this embodiment is formed by a solution method using only metal alkoxide salt as the raw material salt of the chemical solution, as described below, and then fired in an oxygen atmosphere. The amount of carbon contained in the ferroelectric film thus formed was measured by secondary ion mass spectrometry and found to be approximately 1.4 mol %, a low carbon content of less than 2.0 mol %. In other words, the insulating properties of the ferroelectric film according to this embodiment are thought to be improved by using raw materials that do not easily leave carbon in the film after firing and by firing the film for a long period of time in an oxygen atmosphere. Since the ferroelectric film according to this embodiment is formed by a solution method, it becomes a polycrystalline film with an average grain size of less than approximately 10 nm.

[0019] The leakage current was measured for a ferroelectric film containing about 1.4 mol % of carbon. membrane3 shows a leakage current-electric field curve. In FIG. 3, the horizontal axis represents the electric field, and the vertical axis represents the leakage current. The leakage current-electric field curve shown in FIG. 3 shows that the leakage current can be significantly reduced to approximately 9.7×10-8 A / cm2 or less at an electric field of approximately 1 MV / cm. Therefore, the ferroelectric film according to this embodiment has sufficient insulating properties. Note that the state in which an electric field of approximately 1 MV / cm is applied to the ferroelectric film corresponds to a ferroelectric switch state in which the polarization direction of the ferroelectric film switches, as shown in FIG. 2.

[0020] For comparison, we measured the polarization-electric field curve and leakage current of a ferroelectric film (comparison object) formed by a solution method using metal acetylacetonate salts as raw salts for the chemical solution and then fired in a vacuum. Specifically, hafnium acetylacetonate and cerium acetylacetonate were used as the metal acetylacetonate salts, and propionic acid was used as the solvent.

[0021] Figure 4 shows the polarization-electric field curve of the comparative ferroelectric film. In Figure 4, the horizontal axis represents the electric field and the vertical axis represents the polarization. As shown in Figure 4, the comparative ferroelectric film has a spontaneous polarization Ps of approximately 4 μC / cm in an electric field of 0 MV / cm. 2 However, the comparative ferroelectric film could not be applied with an electric field up to 3 MV / cm due to dielectric breakdown. Furthermore, the polarization-electric field curve of the comparative ferroelectric film is a slightly rounded curve.

[0022] On the other hand, the ferroelectric film according to the present embodiment has a spontaneous polarization Ps of about 10 μC / cm in an electric field of 0 MV / cm as shown in FIG. 2 The polarization value is saturated by applying an electric field of 3MV / cm, and the polarization is about 20μC / cm. 2 Furthermore, the polarization-electric field curve of the ferroelectric film according to this embodiment is an ideal hysteresis loop.

[0023] When the leakage current of the comparative ferroelectric film was measured, the leakage current was approximately 1.0 × 10 -6 A / cm 2These values ​​are much larger than those of the ferroelectric film according to the present embodiment. Furthermore, the carbon content of the comparative ferroelectric film is large, at approximately 5.0 mol % or more, which is thought to be a factor in the deterioration of the insulating properties of the comparative ferroelectric film. Therefore, by making the carbon content of the ferroelectric film at least less than approximately 5 mol %, the leakage current of the ferroelectric film can be improved.

[0024] The comparative ferroelectric film uses metal acetylacetonate salt as the raw material salt of the chemical solution, which is more difficult to decompose than metal alkoxide salt. Therefore, in the comparative ferroelectric film, the raw material is not decomposed sufficiently, and a large amount of carbon remains in the film, which is thought to deteriorate the insulation properties.

[0025] On the other hand, the ferroelectric film according to this embodiment uses a metal alkoxide salt as the raw salt of the chemical solution, which is easily decomposed even at a relatively low temperature. Therefore, in the ferroelectric film according to this embodiment, it is thought that the decomposition of the metal alkoxide salt proceeds at a low temperature, forming a fine polycrystalline body and resulting in a low carbon content. By using a metal alkoxide salt as the raw salt, the ferroelectric film according to this embodiment is a thin film of hafnium oxide (HfO2) that has good ferroelectric properties even when fired in an oxygen atmosphere.

[0026] As described above, the ferroelectric film according to this embodiment contains hafnium oxide having a fluorite structure, a metal oxide containing one or more elements selected from La, Ce, and Bi, and carbon contained in an amount of less than 5 mol %. Thus, by controlling the carbon content of the ferroelectric film according to this embodiment to less than 5 mol %, it is possible to obtain a ferroelectric film that exhibits ferroelectricity and has high insulating properties. It is preferable that the carbon content of the ferroelectric film be less than 2 mol %. This further reduces the leakage current of the ferroelectric film, thereby obtaining a ferroelectric film with higher insulating properties.

[0027] It is preferable that the average particle size of the polycrystalline material is less than 10 nm, which allows the production of a ferroelectric film that exhibits stronger ferroelectricity than a thin film of hafnium oxide (HfO2) with columnar particles formed by sputtering or ALD (Atomic Layer Deposition).

[0028] The content of the metal oxide is preferably 1 mol % or more and 15 mol % or less, which allows the HfO2 film to contain an appropriate amount of element-substituted metal oxide, resulting in a ferroelectric film exhibiting stronger ferroelectricity.

[0029] The manufacturing method according to the present embodiment is a method for manufacturing a ferroelectric film containing hafnium oxide. The manufacturing method includes the steps of preparing a film-forming target, preparing a chemical solution that serves as a raw material for the ferroelectric film, spin-coating the chemical solution onto the film-forming target, and precipitating hafnium oxide having a fluorite structure from the chemical solution spin-coated on the film-forming target by heat treatment in an oxygen atmosphere. The chemical solution contains, as raw material salts, a metal alkoxide salt containing Hf and a metal alkoxide salt containing one or more elements selected from La, Ce, and Bi. As a result, the manufacturing method according to the present embodiment can manufacture a ferroelectric film that exhibits ferroelectricity and has high insulating properties.

[0030] [Capacitor using ferroelectric film] Next, the configuration of a capacitor using a ferroelectric film according to this embodiment and a manufacturing method thereof will be described. Fig. 5 is a diagram showing a capacitor 100 using a ferroelectric film according to this embodiment. Note that Fig. 5 shows a cross-sectional view of the capacitor 100.

[0031] The capacitor 100 includes a substrate 1, a first electrode 2, a dielectric layer 3, and a second electrode 4. The material, characteristics, thickness, etc. of the substrate 1 are arbitrary. In this embodiment, for example, a Si(100) substrate with a thickness of 500 μm is used as the substrate 1.

[0032] The first electrode 2 is formed on the substrate 1. The material, characteristics, thickness, etc. of the first electrode 2 are arbitrary. In this embodiment, for example, a Pt film with a thickness of 100 nm is used for the first electrode 2.

[0033] The dielectric layer 3 is formed on the first electrode 2. The ferroelectric film according to this embodiment is used for the dielectric layer 3. That is, the dielectric layer 3 contains hafnium oxide having a fluorite structure, a metal oxide containing one or more elements selected from La, Ce, and Bi, and carbon in an amount of less than 5 mol %. In this embodiment, for example, a ferroelectric film with a thickness of 60 nm is used for the dielectric layer 3.

[0034] The dielectric layer 3 has ferroelectricity, and therefore, the polarization state (polarization direction of spontaneous polarization) of the dielectric layer 3 can be controlled by applying an electric field, and signals can be stored.

[0035] The second electrode 4 is formed on the dielectric layer 3. The material, characteristics, thickness, etc. of the second electrode 4 are arbitrary. In this embodiment, for example, a Pt film with a thickness of 100 nm is used for the second electrode 4.

[0036] The capacitor 100 having the above structure can control the polarization state by applying an electric field, and can be used as a memory device.

[0037] Next, a description will be given of a method for manufacturing the capacitor 100. First, the substrate 1 is prepared. In addition, in parallel with the preparation of the substrate 1, a chemical solution is prepared.

[0038] As raw material salts for the chemical solution, 0.642 g of hafnium isopropoxide and 0.080 g of cerium isopropoxide, which are metal alkoxide salts, are prepared.

[0039] Also, prepare 2 ml of acetic acid and 4 ml of 2-methoxyethanol as solvents for the chemical solution.

[0040] Acetic acid and 2-methoxyethanol are placed in a container and stirred. Each raw salt is then added to the container and stirred to obtain a chemical solution.

[0041] Next, the first electrode 2 made of a Pt film is formed on the substrate 1 by sputtering.

[0042] Next, a chemical solution is coated on the first electrode 2 by spin coating. Specifically, for the first coating, the substrate 1 with the first electrode 2 formed thereon is attached to a turntable, and while the turntable is rotating at 3,000 rpm, a chemical solution is dripped onto the first electrode 2, coating the first electrode 2 with a 20 nm thick film of the chemical solution. The amount of the dripped chemical solution is one-third of the amount of the prepared chemical solution. Next, the substrate 1 with the film of the chemical solution formed on the first electrode 2 is heated to 500°C at a heating rate of 300°C / min in an oxygen atmosphere with an oxygen flow rate of 200 ml / min, and held at that temperature for 10 minutes. As a result, a first HfO2 film is formed on the first electrode 2.

[0043] Next, as the second coating, a chemical solution is applied to the first HfO2 film by spin coating under the same conditions as the first, and then heated to form a second HfO2 film. The amount of the chemical solution applied is one-third of the amount of the prepared chemical solution.

[0044] Next, as the third coating, a chemical solution is applied to the second HfO2 film by spin coating under the same conditions as the first and second coatings, and then heated to form a third HfO2 film. The amount of the chemical solution applied is one-third of the amount of the prepared chemical solution.

[0045] As a result, a dielectric layer 3 is formed on the first electrode 2, in which the first HfO2 film, the second HfO2 film, and the third HfO2 film are laminated to the same thickness.

[0046] Next, the second electrode 4 made of a Pt film is formed on the dielectric layer 3 by sputtering.

[0047] Next, a heat treatment is performed to improve the crystallinity of the dielectric layer 3 (HfO2 film). Specifically, the substrate 1 on which the first electrode 2, dielectric layer 3, and second electrode 4 are formed is heated to 800°C at a temperature increase rate of 300°C / min in an oxygen atmosphere with an oxygen flow rate of 200 ml / min, and held at that temperature for 10 minutes. This completes the capacitor 100.

[0048] As described above, a capacitor 100 can be considered as an example of an electronic component including the ferroelectric film according to this embodiment and an electrode formed on the surface of the ferroelectric film. The capacitor 100 includes a first electrode 2 formed on one main surface of the dielectric layer 3, which is a ferroelectric film, and a second electrode 4 formed on the other main surface of the dielectric layer 3, which is also a ferroelectric film, and is composed of the first electrode 2, the dielectric layer 3, which is also a ferroelectric film, and the second electrode 4. This makes it possible to realize a capacitor 100 whose polarization state can be controlled by applying an electric field, and the capacitor 100 can be used as a memory device.

[0049] [Transistors using ferroelectric films] Next, the configuration of a transistor using a ferroelectric film according to this embodiment and a manufacturing method thereof will be described. Fig. 6 is a diagram showing a transistor 200 using a ferroelectric film according to this embodiment. Note that Fig. 6 shows a cross-sectional view of the transistor 200.

[0050] The transistor 200 is a ferroelectric gate transistor and functions as a memory element. The transistor 200 includes a substrate 1, a gate electrode 20, a gate insulating film 30, a channel forming film 40, a source electrode 50, and a drain electrode 60. The material, characteristics, thickness, etc. of the substrate 1 are arbitrary. In this embodiment, for example, a Si(100) substrate with a thickness of 500 μm is used as the substrate 1.

[0051] The gate electrode 20 is formed on the substrate 1. The gate electrode 20 may be made of any material, have any characteristics, have any thickness, etc. In this embodiment, for example, a Pt film having a thickness of 80 nm is used for the gate electrode 20.

[0052] The gate insulating film 30 is formed on the substrate 1 and the gate electrode 20. The ferroelectric film according to this embodiment is used for the gate insulating film 30. That is, the gate insulating film 30 contains hafnium oxide having a fluorite structure, a metal oxide containing one or more elements selected from La, Ce, and Bi, and carbon in an amount of less than 5 mol %. In this embodiment, for example, a ferroelectric film having a thickness of 60 nm is used for the gate insulating film 30.

[0053] The gate insulating film 30 has ferroelectricity. Therefore, the transistor 200 using a ferroelectric film for the gate insulating film 30 is a ferroelectric gate transistor, and the polarization state (polarization direction of spontaneous polarization) can be controlled by the electric field applied to the gate electrode 20, allowing it to function as a memory element that stores signals.

[0054] The channel formation film 40 is formed on the gate insulating film 30. The material, characteristics, thickness, etc. of the channel formation film 40 are arbitrary. In this embodiment, for example, an ITO film with a thickness of 10 nm is used as the channel formation film 40.

[0055] The source electrode 50 and the drain electrode 60 are formed on the channel formation film 40. The source electrode 50 and the drain electrode 60 may be made of any material, have any characteristics, or have any thickness. In this embodiment, for example, a Pt film having a thickness of 80 nm is used for the source electrode 50 and the drain electrode 60. The source electrode 50 and the drain electrode 60 are formed at positions that straddle the gate electrode 20 when viewed in a plan view from the stacking direction of the transistor 200.

[0056] Next, a method for manufacturing the transistor 200 will be described. First, the substrate 1 is prepared. In addition, a chemical solution is prepared in parallel with the preparation of the substrate 1. Note that the raw material salts for the chemical solution, the solvent for the chemical solution, and the method for obtaining the chemical solution are the same as those for the capacitor 100, and therefore detailed description thereof will not be repeated.

[0057] Next, a platinum (Pt) gate electrode 20 with a film thickness of 80 nm is formed on the substrate 1. Specifically, the gate electrode 20 is formed by forming a photoresist of a predetermined pattern on the substrate 1 using photolithography technology, then depositing platinum (Pt) by radio frequency (RF) sputtering, and removing the photoresist by lift-off.

[0058] Next, a gate insulating film 30 having a thickness of 60 nm is formed on the surface of the substrate 1 on which the gate electrode 20 has been formed. Specifically, the gate insulating film 30 is formed by spin-coating a prepared chemical solution onto the surface of the substrate 1 on which the gate electrode 20 has been formed using a chemical solution deposition (CSD) method, drying at 150°C, and then baking at 800°C in an oxygen atmosphere to crystallize the film.

[0059] Next, a channel formation film 40 with a thickness of 10 nm is formed on the gate insulating film 30. Specifically, the channel formation film 40 is formed by using chemical solution deposition (CSD) to spin-coat an ITO solution on the gate insulating film 30, drying it at 150°C, and then baking it at 500°C in an oxygen atmosphere to crystallize it.

[0060] Next, a source electrode 50 and a drain electrode 60 made of platinum (Pt) with a thickness of 80 nm are formed on the channel formation film 40. Specifically, the source electrode 50 and the drain electrode 60 are formed by forming a photoresist of a predetermined pattern on the channel formation film 40 using photolithography technology, then depositing a platinum (Pt) film by radio frequency (RF) sputtering, and removing the photoresist by lift-off.

[0061] The transistor 200 has a structure in which the gate insulating film 30 of an MFS (Metal-Ferroelectric-Semiconductor) type is a ferroelectric film. This allows the transistor 200 to function as a memory element that stores nonvolatile charges in the gate insulating film 30 and can switch the resistance value of the channel formation film 40 between a high resistance state and a low resistance state using the stored charges. Note that the transistor 200 according to this embodiment does not necessarily have to have an MFS type structure.

[0062] Specifically, the operation of the transistor 200 when it functions as a memory element will be described. For example, when writing to the transistor 200, a voltage is applied between the source electrode 50 and the gate electrode 20 to change the polarization direction of the gate insulating film 30. The charge stored in the gate electrode 20 and the channel formation film 40, which function as capacitor electrodes of the memory element, changes depending on the polarization direction of the gate insulating film 30. As a result, the threshold voltage changes depending on the change in the polarization state of the gate insulating film 30, and the current (drain current) flowing from the source electrode 50 to the drain electrode 60 changes.

[0063] For example, in the case where the channel formation film 40 of the transistor 200 contains an N-type semiconductor material, when the threshold voltage changes in the negative direction, the drain current increases when the voltage applied to the gate electrode 20 (gate voltage) is 0 (zero) V. On the other hand, when the threshold voltage changes in the positive direction, the drain current decreases when the gate voltage is 0 (zero) V. This allows the transistor 200 to alternate between two states: a state in which the drain current is high (on state) and a state in which the drain current is low (off state).

[0064] Therefore, the transistor 200 alternately switches between an on state and an off state by utilizing changes in the polarization state of the gate insulating film 30, thereby storing or erasing signals between the source electrode 50 and the drain electrode 60 and the gate electrode 20.

[0065] Fig. 7 is a diagram showing the electrical characteristics of a transistor 200 using a ferroelectric film according to an embodiment. In Fig. 7, a semiconductor parameter analyzer was used to measure the change in drain current (transfer characteristics) when the voltage (gate voltage) applied to the gate electrode 20 of the transistor 200 was scanned. In measuring the transfer characteristics shown in Fig. 7, the gate voltage VG was scanned in the range of -10 V to +10 V with the drain voltage fixed at 1 V.

[0066] As shown in FIG. 7, the transfer characteristics of the transistor 200 are such that the drain current increases and decreases rapidly with polarization inversion of the gate insulating film 30, and the drain current exhibits a hysteresis with respect to the gate voltage.

[0067] As described above, a transistor 200 can be considered as an example of an electronic component including the ferroelectric film according to this embodiment and an electrode formed on the surface of the ferroelectric film. The transistor 200 includes a gate electrode 20, a source electrode 50, and a drain electrode 60, and the ferroelectric film is formed on the gate electrode 20 as the gate insulating film 30 of the ferroelectric gate transistor. This makes it possible to realize a transistor 200 whose polarization state can be controlled by applying an electric field, and the transistor 200 can be used as a memory element.

[0068] The embodiments disclosed herein should be considered to be illustrative in all respects and not restrictive. The scope of the present invention is defined by the claims, not by the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0069] 1 substrate, 2 first electrode, 3 dielectric layer, 4 second electrode, 20 gate electrode, 30 gate insulating film, 40 channel forming film, 50 source electrode, 60 drain electrode, 100 capacitor, 200 transistor.

Claims

1. Hafnium oxide having a fluorite structure; A metal oxide having one or more elements selected from La, Ce, and Bi; and carbon contained in an amount of less than 5 mol %, The ferroelectric film is a polycrystalline body having an average grain size of less than 10 nm.

2. The ferroelectric film according to claim 1 , wherein the metal oxide is contained in an amount of 1 mol % or more and 15 mol % or less.

3. The ferroelectric film according to claim 1 or 2, and an electrode formed on a surface of the ferroelectric film.

4. the electrodes include a first electrode formed on one main surface of the ferroelectric film and a second electrode formed on the other main surface of the ferroelectric film; 4. The electronic component according to claim 3, wherein the first electrode, the ferroelectric film, and the second electrode form a capacitor.

5. the electrodes include a gate electrode, a source electrode, and a drain electrode; 4. The electronic component according to claim 3, wherein the ferroelectric film is formed on the gate electrode as a gate insulating film of a ferroelectric gate transistor.

Citation Information

Patent Citations

  • Electronic device

    JP2020035952A

  • Method for depositing hafnium lanthanum oxide film on substrate by circulation deposition process in reaction chamber

    JP2020133002A

  • CAPACITOR AND METHOD FOR MANUFACTURING HfO 2 FILM

    WO2019208340A1

  • Method for producing ferroelectric film, ferroelectric film, and usage thereof

    WO2020218617A1